To investigate the effect of age and body mass index on blood pressure in menopausal and premenopausal women - Meenu Rani; Lokendra Sharma; Kopal Sharma; Susheel Kumar (Wolters Kluwer Medknow Publications, 2020)
Objectives: The objective of the study is to examine the effect of age and body mass index (BMI) on blood pressure (BP) in menopausal and premenopausal women. Methods: Five hundred and thirty women between the age groups of 35 and 60 years were taken. The association between BMI and BP was measured using simple linear regression. Student's t-test was used for intragroup comparison. Results: Systolic BP (P = 0.008) and diastolic BP (P = 0.004) were slightly but significantly higher in menopausal women as compared to premenopausal women. Obesity was found to be more in menopausal women than premenopausal women (P < 0.01). Conclusion: It can be concluded that higher BMI and age lead to higher BP in menopausal women.